Globalization, Economic Freedom, and Wage Inequality: A Panel Data Analysis - Yay, Gulsun; Tastan, Huseyin; Oktayer, Asuman (SAVEZ EKONOMISTA VOJVODINE, 2016)
This paper examines the impact of globalization and liberalization on wage inequality using the KOF globalization index, the Economic Freedom Index (EFI) of the Fraser Institute and the Theil industrial pay inequality statistic compiled by the University of Texas Inequality Project (UTIP). Both static and dynamic fixed-effects models are estimated using a 5-year panel data set consisting of about 90 developed and developing countries for the 1970-2005 period. Estimation results from the dynamic panel data specification suggest that wage inequality has a significant and slowly changing component. The overall KOF and EFI indexes are found to be statistically insignificant in the full sample, but the results show that economic freedom is associated with more wage inequality, especially in Organisation for Economic Co-operation and Development (OECD) countries. The estimation results from country groups indicate that more deregulation is associated with more earnings inequality in OECD countries. The results from the models with subcomponents of the EFI imply that access to sound money has a negative effect on wage inequality. A more stable price system in an economy implies a more equal wage distribution in emerging markets (EM), non-OECD countries, and European Union (EU).
Keywords: Wage inequality; Globalization; Economic freedom; INCOME-DISTRIBUTION; INFLATION; IMPACT; TRADE; Business & Economics